2005
DOI: 10.1523/jneurosci.2381-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation-Dependent Polymerization Is an Essential Component of Amyloid-Mediated Neuronal Cell Death

Abstract: Accumulating evidence suggests that amyloid protein aggregation is pathogenic in many diseases, including Alzheimer's disease. However, the mechanisms by which protein aggregation mediates cellular dysfunction and overt cell death are unknown. Recent reports have focused on the potential role of amyloid oligomers or protofibrils as a neurotoxic form of amyloid-␤ (A␤) and related amyloid aggregates. Here we describe studies indicating that overt neuronal cell death mediated by A␤ 1-40 is critically dependent on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
170
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(186 citation statements)
references
References 46 publications
(64 reference statements)
14
170
2
Order By: Relevance
“…Similarly, using SEC-isolated Aβ42 protofibrils, we have shown that monomeric Aβ40 inhibited Aβ42 protofibril toxicity toward cultured neurons by altering their aggregation properties and inhibiting fibril formation. These observations reinforced the importance of an ongoing Aβ-nucleated polymerization as a critical factor for Aβ-induced toxicity 21,66 .…”
Section: High Molecular Weightsupporting
confidence: 62%
“…Similarly, using SEC-isolated Aβ42 protofibrils, we have shown that monomeric Aβ40 inhibited Aβ42 protofibril toxicity toward cultured neurons by altering their aggregation properties and inhibiting fibril formation. These observations reinforced the importance of an ongoing Aβ-nucleated polymerization as a critical factor for Aβ-induced toxicity 21,66 .…”
Section: High Molecular Weightsupporting
confidence: 62%
“…The different behavior of A-oligomers (non-toxic) with respect to A+ oligomers (toxic) was confirmed in human SH-SY5Y neuroblastoma cells by using the MTT assay (Fig. 1B), taking into account some concerns regarding a nonspecific interference of A␤ peptide with MTT reduction [54]. However, A-oligomers become significantly toxic in cells enriched in GM1 content by a factor of ca.…”
Section: Harmless Aβ 42 Oligomers Become Toxic In Gm1-enriched Neuronmentioning
confidence: 71%
“…We first compared the toxic properties of the purified α-syn species in human dopaminergic neuroblastoma cell lines (M17 and SH-S5Y5 cells). Using the uptake of the vital dye propidium iodide (PI) as a marker for membrane disruption and toxicity, in combination with flow cytometry quantification, we observed that neither α-syn monomers ( Although several studies have shown that different aggregated forms of α-syn exhibit toxicity in various cellular 17,20,23,32 and in vivo models, 12,32 increasing evidence from our group 27,33 and others 34 suggest that amyloid toxicity could be linked to the process of amyloid formation rather than to specific aggregated forms of amyloidogenic proteins. To determine whether this applies to α-syn-induced toxicity, we assessed the effect of inducing fibril growth by the addition of α-syn PFFs (10%) to monomeric α-syn solutions.…”
Section: Resultsmentioning
confidence: 89%